2010
DOI: 10.1519/jsc.0b013e3181f00d22
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Anthropometric Correlates of Tackling Ability in Junior Elite and Subelite Rugby League Players

Abstract: This study investigated the tackling ability of junior elite and subelite rugby league players, and determined the relationship between selected physiological and anthropometric characteristics and tackling ability in these athletes. Twenty-eight junior elite (mean ± SD age, 16.0 ± 0.2 years) and 13 junior subelite (mean ± SD age, 15.9 ± 0.6 years) rugby league players underwent a standardized 1-on-1 tackling drill in a 10-m grid. Video footage was taken from the rear, side, and front of the defending player. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
75
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 20 publications
8
75
2
2
Order By: Relevance
“…13,14 Studies in Australia and the UK have shown that a number of age, anthropometric and skill-based traits can distinguish players participating at the elite and national representative level from those in sub-elite and regional teams. 14,15 Maturation was also a strong confounder in the UK study, which highlights the impact of pubertal stage on junior rugby league performance. 14 Despite extensive research at this level of competition, no studies have comprehensively documented the anthropometric characteristics of junior elite rugby league players using somatotype and international guidelines for kinanthropometry.…”
Section: Introductionmentioning
confidence: 87%
“…13,14 Studies in Australia and the UK have shown that a number of age, anthropometric and skill-based traits can distinguish players participating at the elite and national representative level from those in sub-elite and regional teams. 14,15 Maturation was also a strong confounder in the UK study, which highlights the impact of pubertal stage on junior rugby league performance. 14 Despite extensive research at this level of competition, no studies have comprehensively documented the anthropometric characteristics of junior elite rugby league players using somatotype and international guidelines for kinanthropometry.…”
Section: Introductionmentioning
confidence: 87%
“…Gabbett, Kelly, and Pezet (2007) investigated the fitness and skill levels of 86 sub-elite (amateur) rugby league players and demonstrated that skill, but not physical qualities, discriminated successful (i.e., subelite first grade) from less successful (i.e., sub-elite second and third grade) players. In a subsequent study, significant differences were reported between professional and semi-professional (Gabbett & Ryan, 2009) and high-skilled and lesser-skilled junior (Gabbett, Jenkins, & Abernethy, 2010) rugby league players on a standardised assessment of tackling proficiency. It was also shown that a dual-task assessment of draw and pass ability (i.e., performance of the skill coupled with a secondary tone recognition task) discriminated higher and lesser-skilled junior rugby league players, when performance of the draw and pass assessment in isolation did not (Gabbett, Wake, & Abernethy, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Due to the physically demanding nature of rugby league, players are required to have highly developed physiological capacities of muscular strength, power, speed, agility and endurance alongside increased lean mass (Gabbett & Seibold, 2013;Johnston et al, 2014). Like many sports, TID research within rugby league has predominantly compared the abilities of players of differing playing levels (i.e., elite vs. sub-elite), showing anthropometric and fitness characteristics increase with playing level within junior players (Gabbett, 2009;Gabbett, Jenkins & Abernethy, 2010;Till et al, 2011). In addition, further research (Till, Cobley, O'Hara, Chapman & Cooke, 2010a;Till, Cobley, O'Hara, Chapman & Cooke, 2010b;Till, Cobley, O'Hara, Chapman & Cooke, 2014b) has also suggested that there are a number of 5 independent factors (i.e., annual-age category, relative age, maturation and playing position) that influence the selection of players to TID programmes within youth rugby.…”
Section: Introductionmentioning
confidence: 99%